Effect of foliar application of silicon on some Characteristics Development of the grain product drying system by adapting a microcontroller - Azizbek Nodirbekovich Yusupbekov; Dilmurod Ikromovich Egamberganov (Zien Journals, 2022)
The duration of drying processes is considerable in time, from 8 to 36 hours, and it can be assumed that unforeseen circumstances are likely to occur in this interval. For this reason, and also during the setting of the temperature regulators in the system, the possibility of remote monitoring and changing its parameters was sought. In the proposed version of the process control system in the experimental convective dryer, a personal computer with a Windows operating system and MATLAB and LabVIEW software packages are used.
Keywords: convective dryer; grain; microcontroller; WEB application